The effects of modulating potassium(ATP) channel activity in normal and 1-week denervated mouse EDL and soleus muscles. - Matar, Wadih Y. (University of Ottawa (Canada), 2000)
During exercise, the metabolic rate of muscle increases considerably, and hence the concentration of various metabolites is altered. Surprisingly, the concentration of ATP is not decreased significantly even at exhaustion. This suggests that the muscle may have a safety mechanism that shuts down force generation in order to avoid energy depletion, as the latter causes irreversible damage to the muscle cell. The K+(ATP) channel, which is activated by decreased ATP levels, might be involved in this safety mechanism. According to its postulated mechanism, once activated the channel can contribute to decreasing force generation by decreasing the excitability of the muscle membrane. The scope of this thesis will deal with the physiological role of the K+(ATP) channel in skeletal muscle during fatigue. The main objectives of this study were to understand the physiological role of the K+(ATP) channel and how this role is affected by 1-week denervation in mouse EDL and soleus muscles. K +(ATP) channels were either blocked with 10 muM glibenclamide, or activated with 100 muM pinacidil, while muscles were fatigued by tetanic contractions every sec for 3 min. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.